Antagonisme Bacillus terhadap Infeksi Layu Fusarium pada Bibit Pisang Hasil Kultur Jaringan - Hadiwiyono Hadiwiyono; Arief Widyantoro; Salim Widono (Agrosains : Jurnal Penelitian Agronomi, 2013)
Fusarium wilt (Fusarium oxysporum f.sp. cubense) is an important disease in banana. Fusarium wilt was hard to control because the pathogen can survive in many kind of soils type although there is no host. Therefore, overcoming the disease is urgently needed such as biological control. The endophytic Bacillus of banana was begun to use as antagonist agent to the pathogen. This research aimed to study the mechanism of antagonism and physiological character of Bacillus. There were 27 Bacillus isolates examined in-vitro to test the production of IAA, HCN, chitinase, pectinase, and antagonism. The top ten isolates based on the test in vitro were used to test in planta. The research showed that Bacillus were able to produce IAA, HCN, chitinase, pectinase, and able to retard the growth of Foc colony. The application of isolat B25 on banana seedling could decrease the disease intensity but still unable to prevent the fusarium wilt infection.